(untitled) - Mettrick, Hal (Wageningen, Netherlands, 1993)
This book introduce about the role of development oriented research, planning research programmes and projects, a farming systems approach, approaches to the study of farming systems, choice of survey methods...
Keywords: Agricultural systems,Agriculture; Research